Basic architecture of design of digital twins for construction (2022)
Digital twins replicate the functioning of an object or process in a virtual model that serves as the basis for experimentation. Building Information Models (BIM), are driving the digitization of the construction sector through the use of multidisciplinary models and collaboration in the cloud. The aim of this study is to offer an approach for the incremental design of a digital twins based on BIM technology, to achieve a total operational management of the construction facility. The conceptual elements of digital twins are offered, with emphasis on their character as a virtual model, which includes simulation of the behavior of their physical twin in real time. The main existing approaches for incremental design of BIM-based digital twins are also revealed and a general architecture is presented, which is based on a minimum viable maturity level for early adopters of this technology.